2015
DOI: 10.1037/a0039435
|View full text |Cite
|
Sign up to set email alerts
|

Social conditioned place preference in the captive ground squirrel (Ictidomys tridecemlineatus): Social reward as a natural phenotype.

Abstract: Social behaviors of wild animals are often considered within an ultimate framework of adaptive benefits versus survival risks. By contrast, studies of laboratory animals more typically focus on affective aspects of behavioral decisions, whether a rodent derives a rewarding experience from social encounter and how this experience might be initiated and maintained by neural circuits. Artificial selection and inbreeding have rendered laboratory animals more affiliative and less aggressive than their wild conspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 124 publications
1
11
0
Order By: Relevance
“…However, in the social CPP test, captive juveniles that were second- and third-generation descendants of wild ground squirrels expressed a robust preference for environments paired with social access, indicating that social interactions can be rewarding for rodents with undomesticated genetic backgrounds (Lahvis et al 2015). This finding suggests that wild squirrels, known for their diminished sociality, can derive pleasure from a social interaction.…”
Section: Social Rewardmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the social CPP test, captive juveniles that were second- and third-generation descendants of wild ground squirrels expressed a robust preference for environments paired with social access, indicating that social interactions can be rewarding for rodents with undomesticated genetic backgrounds (Lahvis et al 2015). This finding suggests that wild squirrels, known for their diminished sociality, can derive pleasure from a social interaction.…”
Section: Social Rewardmentioning
confidence: 99%
“…This finding suggests that wild squirrels, known for their diminished sociality, can derive pleasure from a social interaction. Additional comparisons of laboratory experiments with concurrent field experiments showed that while maturing wild juveniles gradually foraged at increasing distances from one another, a behavioral pattern that predicts dispersal, captive juveniles simultaneously expressed diminished social approach and increased play fighting (Lahvis et al 2015). Taken together, this comparison supports the idea that the adolescent thirteen-lined ground squirrel can experience social reward and that social motivation diminishes as maturing adolescents begin to disperse, an idea akin to the “ontogenetic switch” (Holekamp 1984).…”
Section: Social Rewardmentioning
confidence: 99%
See 2 more Smart Citations
“…Place conditioning has been used to demonstrate the pleasurable aspects of (playful) social interactions (Calcagnetti and Schechter, 1992; Crowder and Hutto, 1992; Douglas et al, 2004; Lahvis et al, 2015; Panksepp and Lahvis, 2007; Van den Berg et al, 1999b), access to pups (Mattson et al, 2001), sexual behaviour (Camacho et al, 2004; Jenkins and Becker, 2003; Kippin and van der Kooy, 2003), as well as aggressive social interactions (Martinez et al, 1995; Tzschentke, 2007). …”
Section: Introductionmentioning
confidence: 99%